Seismo-tectonics of the Shillong Plateau - a geodynamic perspective through remote sensing - Duarah, BP; Phukan, S (Journal of Nepal Geological Society, 2008)
The Shillong Plateau of Northeastern part of India is tectonically and geologically interesting entity in the subducted front of Indian Plate below the Burmese Plate to the southeast and Tibetan Plate to the north, due to the northeastern journey of the Indian Plate. Structural features, like horse-tail geometry in the Dafala Hills, east of the Jia Bhareli river, associated with south-convex foothill ranges in the eastern Himalaya and exactly similar structural geometry in the eastern part of Shillong Plateau in Meghalaya seems to develop due to high resistance received by the Shillong Plateau in its eastward journey, which is possibly accompanied by clockwise rotation of the plateau. The wide separation of the Karbi Anglong Plateau and the Shillong Plateau to the southeast as compared to the northwestern part seems to represent the shape of the Kopili Graben. Low seismic activity in the southeastern part of the Shillong Plateau might be related to the stress released field generated by its clockwise rotation. In conformity with this fact, high concentration of epicenters is observed in the northwestern part of the Kopili graben, in the central Brahmaputra valley, as a result of stress development. The structural interpretation of Landsat ETM+ and SRTM data shows that the central part of the Shillong Plateau possesses young topography with strong structural fabrics along with relatively high topography aligning NE-SW following the Kolkota-Pabna- Mymansingh High and if extended passes through Bomdila in the Himalayas. This alignment has been observed in the Precambrian Gneissic Complex west of the Proterozoic intracratonic Shillong Basin. The epicentral plots from 1918 to June 2007 show their high concentration within the Shillong Plateau aligning along this trend. The active geodynamics of Shillong Plateau is reflected in its seismic activity. It is observed that the Brahmaputra river in the plateau frontbetween Palasbari (91°30' 39"E: 26°06'58"N) and Goalpara (90°37'47"E: 26°11'01"N) has been shifted by more than 5 km to the north during the period from 1911-2002, which otherwise a south migrating river. This is also supported by shrinking pattern of Sandubi (Chandubi) Lake in the Kulsi river catchment, a north-flowing tributary of the Brahmaputra in the north-central part of the plateau. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.3